Significant Suppression of Non-small-cell Lung Cancer by Hydrophobic Poly(ester amide) Nanoparticles with High Docetaxel Loading - Chen, Xing; Zhao, Lili; Kang, Yang; He, Zhiyu; Xiong, Fei; Ling, Xiang; Wu, Jun (Frontiers in Pharmacology, 2018)
Non-small-cell lung cancer (NSCLC) accounts for over 85% of clinical lung cancer cases, which is the leading cause of cancer-related death. To develop new therapeutic strategy for NSCLC, a library of L-phenylalanine-based poly(ester amide) (Phe-PEA) polymers was synthesized and assembled with docetaxel (Dtxl) to form Dtxl-loaded Phe-PEA nanoparticles (NPs). The hydrophobic Phe-PEA polymers were able to form NPs by nanoprecipitation method and the characterization results showed that the screened Dtxl-8P4 NPs have small particle size (∼100 nm) and high Dtxl loading (∼20 wt%). In vitro experiments showed that Dtxl-8P4 NPs were rapidly trafficked into cancer cells, then effectively escaped from lysosomal degradation and achieved significant tumor cell inhibition. In vivo results demonstrated that Dtxl-8P4 NPs with prolonged blood circulation could efficiently deliver Dtxl to A549 tumor sites, leading to reduced cell proliferation, block metastasis, and increase apoptosis, then persistent inhibition of tumor growth. Therefore, Phe-PEA NPs are able to load high amount of hydrophobic drugs and could be a promising therapeutic approach for NSCLC and other cancer treatments.